Perkembangan Konsep Perjanjian Production Sharing Contract Dalam Mekanisme Pengolahan Minyak dan Gas di Indonesia - Mohammad Choirul Anam; Retno Catur Kusuma Dewi; Angga Pramodya Pradhana (Universitas Merdeka Madiun, 2024)
This research aims to determine the development of the concept of agreements in production sharing contracts in the oil and gas processing sector based on legal principles in Indonesia. This research uses normative juridical research which uses statutory regulations as a secondary data source. Apart from that, journals, articles, news portals (websites) were also used as supporting sources in this research. Based on the research results, it was found that the development of the concept of production sharing contracts in the oil and gas processing sector in Indonesia was initially introduced by Ibnu Sutowo. Then as time went by it developed up to 4 (four) changes. Even though in its development there have been changes, the concept used in the agreement remains the same, the only difference is in the type of agreement. The concept of a production sharing agreement can be applied in Indonesia because it is simpler, easier to understand by the public, more cost effective; compared to the “Profit Sharing” mechanism. The amount of